Host-dependent functional response of Typhlodromus bagdasarjani (Acari: Phytoseiidae) feeding on Tetranychus urticae (Acari: Tetranychidae) - Afsoon Azadi-Qoort; Amin Sedaratian-Jahromi; Azadeh Farazmand (Persian Journal of Acarology)
Typhlodromus (Anthoseius) bagdasarjani Wainstein & Arutunjan is an indigenous species naturally inhabiting mulberry and fig trees in urban regions. The current study was conducted to evaluate possible effects of four host plants including cucumber, tomato, eggplant, and watermelon on the functional response of T. bagdasarjani feeding on different densities (2, 4, 8, 16, 32, 64, and 128) of immature stages (larva + protonymph) of Tetranychus urticae Koch. The experiments were conducted under laboratory conditions at 25 ± 1 ℃, 60 ± 5% RH, and a photoperiod of 16:8 (L:D) h. The logistic regression revealed type II functional response on the tomato, eggplant, and watermelon and a type III one on the cucumber. The handling time (Th) and searching efficiency (a) were estimated using the Rogers equation. The highest and lowest values of Th in the type II functional response were recorded on the watermelon (0.927 ± 0.061 h) and eggplant (0.632 ± 0.085 h), respectively. Accordingly, the highest and lowest values of searching efficiency in this type of functional response were obtained on the watermelon (0.055 ± 0.009 h−1) and eggplant (0.028 ± 0.005 h−1), respectively. The maximum predation rate (T/Th) was recorded on the eggplant (37.963 prey/day). On the cucumber, the value estimated for the handling time was 1.341 ± 0.079 h. The maximum predation rate on this host plant was estimated to be 17.90 prey/day. In conclusion, our findings revealed effects of different host plants on the functional response of T. bagdasarjani showing that this species may be more effective in suppressing the population of T. urticae on the cucumber.